POTENTIAL ATTRACTION OF SEPAHAT BEACH BANDAR LAKSAMANA BENGKALIS REGENCY - Muhammad Rizal Efendi; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Sepahat Village has a beautiful beach called Sepahat Beach, where this beach is always crowded with visitors during the day and at night, because here there is a cafe on the beach sand and a long bridge is provided that leads directly to the open sea, so that when the tide is going up will add to the sensation of relaxing in this cafe and bridge. The purpose of this research is to find out the tourist attraction of Sepahat Beach and to know the potential of the tourist attraction of Sepahat Beach. This study uses a qualitative method with a descriptive approach, in which the researcher tries to describe the actual conditions and circumstances by collecting data and information in the field. The research subjects of this study were the Sepahat village government, the Sepahat Village Bumdes, the Head of the Bengkalis Regency Office and visitors to Sepahat Beach. The research results obtained are that Sepahat Beach has a unique natural attraction that is different from other marine tourism, adequate facilities and infrastructure, road access and strategic location, good socio-cultural community, and supported by interesting activities and events. The potential for the tourist attraction of Sepahat Beach is that it can improve the community's economy, increase regional income, as well as a means of conservation. Keywords: Sepahat Beach, Attractiveness, Potential